From foundational narratives to dissolution narratives. The question of national identity in contemporary cinema - Lúcia Ramos Monteiro (Galáxia, 2018)
Notwithstanding the extensive discussion questioning concepts like “nation” and “nationalism” within historiography, and the debate about the actuality and functionality of “national cinema” as a category in the lm studies eld (BERRY, 2006), those notions continue to be used by lm scholars, festivals, competitions etc. Contrary to the so-called “foundational narratives” (SOMMER, 2004), in which domestic happiness and national ideal were interwoven, some contemporary lms maintain a strong relation between “individual” and “national” spheres, but in a negative way. This leads us to propose the “dissolution narratives” concept, anchored in Jia Zhangke’s lm analysis, particularly Mountains May Depart (2015).